Mathematical modelling of an elongated magnetic droplet in a rotating magnetic field - Cebers, Andrejs; Kalis, Harijs (Mathematical Modelling and Analysis, 2012)
Dynamics of an elongated droplet under the action of a rotating magnetic field is considered by mathematical modelling. The actual shape of a droplet is obtained by solving the initial-boundary value problem of a nonlinear singularly perturbed partial differential equation (PDE). For the discretization in space the finite difference scheme (FDS) is applied. Time evolution of numerical solutions is obtained with MATLAB by solving a large system of ordinary differential equations (ODE).